Aggregate Index of Systemic Inflammation is Correlated with Plasma Leakage Indicator in Dengue Virus Infection - Jatmiko, Safari; Puspitasari, Metana; Aisyah, Riandini (Universitas Muhammadiyah Surabaya, 2025)
Severe dengue virus infection (DVI) is characterized by thrombocytopenia and plasma leakage (PL) due to the release of vasoactive cytokines by immune cells such as monocytes, lymphocytes, neutrophils, and platelets in response to dengue virus (DENV). This immune response triggers systemic inflammation, altering monocyte, lymphocyte, and neutrophil kinetics, which in turn affects leukocyte differentials. PL is indicated by an increase in hematocrit (Hct). This study aims to evaluate the potential use of the Aggregate Index of Systemic Inflammation (AISI) as an indicator of plasma leakage. A correlative analytical study with a cross-sectional approach was conducted on 70 pediatric DVI patients diagnosed according to the 2009 WHO criteria and confirmed by anti-DENV IgM/IgG tests. Patients with a history of malignancy, autoimmune thrombocytopenic purpura, or secondary DVI were excluded. Absolute neutrophil, monocyte, platelet, and lymphocyte counts, AISI, and Hct levels were obtained from complete blood count results using a hematology analyzer. The results showed that AISI and lymphocytes correlated with Hct, with correlation values of (r=0.410, p<0.001) and (r=0.446, p<0.001), respectively. In contrast, monocytes, neutrophils, and platelets did not correlate with Hct, with correlation values of (r=-0.009, p=0.942), (r=-0.059, p=0.628), and (r=-0.175, p=0.147), respectively. In conclusion, AISI levels in DVI were low and negatively correlated with Hct, a known indicator of PL. These findings suggest that AISI has potential as a marker for PL and disease severity in DVI.